Perceived effectiveness of privacy policy and its association with trust and behavioral intention to participate in a digital workplace wellness program - Peltoniemi, Ari (2020)
The Perceived Effectiveness of Privacy Policy (PEPP) is a topical issue in information privacy research. In this study we developed a research model applying Theory of Reasoned Action and the Privacy–Trust–Behavioral Intention model to measure PEPP and its relationships with Trust and Behavioral Intention to participate in a digital Workplace Wellness Program (WWP). Increased participation in WWPs introduces the potential of increased profits for employers and increased health outcomes for employees. An online survey instrument was developed and used to collect data from the population of Finnish white-collar telecommuters. The Partial Least Squares Path Modeling (PLS-PM) method was used to analyze the data. The results indicate that there are statistically significant positive relationships between the constructs of Security and PEPP, PEPP and Trust, and Trust and Behavioral Intention to Participate in a digital WWP. We identified also statistically significant indirect effects between Security and Trust, Security and Behavioral Intention as well as PEPP and Behavioral Intention to Participate in a digital WWP. The results indicate that efforts to increase PEPP may be justified to increase Trust and Behavioral Intention to participate in a digital WWP among working professionals.